2018
DOI: 10.2478/sjph-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Specialty training in family medicine in Montenegro – An evaluation of the programme by the first generation of trainees

Abstract: IntroductionOne of the aims of health care reform in Montenegro is to strengthen primary care. An important step forward is the implementation of specialty training in family medicine (FM). The aim of this article is to evaluate the implementation of specialty training in family medicine in Montenegro, regarding the content, structure and methods, by the first generation of trainees and the coordinator of the training.MethodsA questionnaire was sent by mail in July and August 2017 to all 26 eligible trainees w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
5
0
2
Order By: Relevance
“…It is interesting to note that trainee physicians working in person with their direct tutor achieve comparatively higher levels of satisfaction with working conditions compared to those whose main tutor is only available by phone. Similar associations regarding the improved satisfaction of medical students were likewise demonstrated in a study on a curricular reform that also entailed better access to tutors (33). "Working with a constant population" is one of the important features of a family physician's work, which is also supported by our results.…”
Section: Discussionsupporting
confidence: 87%
“…It is interesting to note that trainee physicians working in person with their direct tutor achieve comparatively higher levels of satisfaction with working conditions compared to those whose main tutor is only available by phone. Similar associations regarding the improved satisfaction of medical students were likewise demonstrated in a study on a curricular reform that also entailed better access to tutors (33). "Working with a constant population" is one of the important features of a family physician's work, which is also supported by our results.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, it was found that general satisfaction scores of all items ranged between 6.61 and 7.95, which was higher than reported by U Rabbani with a score of 7.61,[ 20 ] a study of Montenegro in which the satisfaction level was 4.1 out of 5[ 25 ] and study in the USA where the satisfaction level was over 50%. [ 26 ]…”
Section: Discussionmentioning
confidence: 86%
“…Improving the satisfaction level of trainers, up to different literature reviews, would improve their performance. [ 20 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…We hope that this report might offer our colleagues reference points for feeding back into their local and national educational boards, with the aim of improving the position of academic FM/GP in Europe. Encouraging reports of these activities already exist ( 10 ).…”
Section: Discussionmentioning
confidence: 99%